Targeted Gene Panel Sequencing for Molecular Diagnosis of Kallmann Syndrome and Normosmic Idiopathic Hypogonadotropic Hypogonadism - Kim, Ja Hye; Seo, Go Hun; Kim, Gu-Hwan; Huh, Juyoung; Hwang, Il Tae; Jang, Ja-Hyun; Yoo, Han-Wook; Choi, Jin-Ho (Experimental and Clinical Endocrinology & Diabetes, 2019)
Background Isolated gonadotropin-releasing hormone (GnRH) deficiency (IGD) is classified either as Kallmann syndrome (KS) with anosmia or normosmic idiopathic hypogonadotropic hypogonadism (nIHH) and caused by mutations in more than 30 different genes. Recent advances in next-generation sequencing technologies have revolutionized the identification of causative genes by using massively parallel sequencing of multiple samples. This study was performed to establish the genetic etiology of IGD using a targeted gene panel sequencing of 69 known human IGD genes.Methods This study included 28 patients with IGD from 27 independent families. Exomes were captured using customized SureSelect kit (Agilent Technologies) and sequenced on the Miseq platform (Illumina, Inc.), which includes a 163,269 bp region spanning 69 genes.Results Four pathogenic and six likely pathogenic sequence variants were identified in 11 patients from 10 of the 27 families (37%) included in the study. We identified two known pathogenic mutations in CHD7 and PROKR2 from two male patients (7.4%). Novel sequence variants were also identified in 10 probands (37%) in CHD7, SOX3, ANOS1, FGFR1, and TACR3. Of these, while eight variants (29.6%) were presumed to be pathogenic or likely pathogenic, the remaining two were classified as variants of uncertain significance. Of the two pre-pubertal males with anosmia, one harbored a novel heterozygous splice site variant in FGFR1.Conclusions The overall diagnostic yield was 37% of the patients who had undergone targeted gene panel sequencing. This approach enables rapid, cost-effective, and comprehensive genetic screening in patients with KS and nIHH.
Keywords: anosmia; normosmic idiopathic hypogonadotropic hypogonadism; kallmann syndrome; next-generation sequencing; targeted gene panel